Establishing the need for clinical follow-up after emergency appendicectomy in the modern era: Retrospective case series of 145 patients. (October 2018) - Som, Robin; Seymour, Nicky; Thrumurthy, Sri G.; Khattak, Sophia; Joshi, Shivani; Sorelli, Paolo G.
Abstract: Introduction: Emergency appendicectomy (EA) is a commonly performed operation, with an increasing number of EAs being performed as day-case. The aim of this study is to establish if there is a need for post-operative follow-up and if this could prevent adverse outcomes. Methods: A retrospective analysis of patients who underwent EA at multiple centres over a six-month period was undertaken. They were contacted by telephone and a standardised questionnaire was used to ascertain post-operative outcomes, including duration of analgesia use, duration before return to normal daily activity (ADLs), surgical site infection rates (SSI) and rates of re-presentation to medical services. Patients were stratified into those who underwent laparoscopic versus open appendicectomy, smokers versus non-smokers, and body mass index (BMI). Results: A total of 145 patients were included in the study. Patients undergoing open surgery (vs. laparoscopic surgery) required analgesia for significantly longer periods, with a significantly longer return to ADLs. Smokers, when compared to non-smokers experienced a significantly longer return to work/school; and significantly higher risk of SSI and re-presenting to accident & emergency; as did patients with a BMI >30 when compared to those with a BMI <30. Conclusion: Most patients do not need formal outpatient assessment after EA. However, there is clearly a subset of higher risk patients who may benefit from this – patients who are smokers or obese. They have prolonged recovery times, and are at greater risk of SSI. Earlier surgical outpatient follow-up of these patients could prevent adverse outcomes. Highlights: It is essential to identify surgical methods or subgroups of patients who are more likely to have poorer outcomes following EA Without follow-up, it is difficult to identify optimal surgical techniques and higher risk groups. This is one of few, recent longitudinal studies with a focus on patient centred outcomes We found that patients who are smokers, who have a BMI >30 or who have open operations are more likely to develop SSI, require more analgesia and return to work later than other patients Higher risk patients should be considered for closer scrutiny in the post-operative phase, perhaps by 'virtual clinic'. If higher risk patients are found earlier in the post-operative period, it may prevent SSIs from developing, therefore shortening the length of return to work or school.